2015
DOI: 10.1504/ijsn.2015.070426
|View full text |Cite
|
Sign up to set email alerts
|

Compression-based analysis of metamorphic malware

Abstract: Compression-based Analysis of Metamorphic Malware by Jared LeeRecent work has presented a technique based on structural entropy measurement as an effective way to detect metamorphic malware. The technique uses two steps, file segmentation and sequence comparison, to calculate file similarity. In another previous work, it was observed that similar malware have similar measures of Kolmogorov complexity. A proposed method of estimating Kolmogorov complexity was to calculate the compression ratio of a given malwar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2

Relationship

4
2

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 24 publications
(49 reference statements)
0
18
0
Order By: Relevance
“…Previous research [2,15] has shown that HMMs trained on opcode sequences and/or function call-graphs can effectively classify different families of malware.…”
Section: Hmm For Malware Detectionmentioning
confidence: 99%
“…Previous research [2,15] has shown that HMMs trained on opcode sequences and/or function call-graphs can effectively classify different families of malware.…”
Section: Hmm For Malware Detectionmentioning
confidence: 99%
“…It has produced good results for polymorphic malware and metamorphic malware [2,16]. Unlike other techniques, this technique will not work on opcode sequence; it works on raw byte of the file.…”
Section: Structural Entropymentioning
confidence: 99%
“…The proposed technique for detection of software piracy is an extension of the technique presented in [2,16]. Our technique can be divided into two major parts: file segmentation and sequence comparison.…”
Section: Structural Entropymentioning
confidence: 99%
See 2 more Smart Citations